Peucedanum japonicum Thunb. ethanol extract suppresses RANKL-mediated osteoclastogenesis - Kim, Jeong-Mi (Exp Ther Med, 2017)
The constituents of Peucedanum japonicum Thunb. (PJ) exhibit biological and pharmacological activities, including anti-obesity, anti-oxidant and anti-allergic activities. The aim of the present study was to examine in vitro effects of PJ in RANKL-induced signaling pathways, which determine osteoclast differentiation. PJ ethanol extract (PEE) exhibited anti-osteoporotic activity by disrupting the phospholipase C (PLC)-Ca2+-c-Fos/cAMP response element-binding protein (CREB)-nuclear factor of activated T cells, cytoplasmic 1 (NFATc1) signaling pathway during osteoclastogenesis. Murine bone marrow-derived macrophages (BMMs) were cultured and used to determine the effects of PJ in the receptor activator of nuclear factor κB ligand (RANKL)-mediated osteoclastogenesis. The effects of PEE in the RANKL-mediated signaling cascade were evaluated using a standard in vitro osteoclastogenesis system. PEE treatment of BMMs significantly reduced the number of RANKL-mediated tartrate resistant acid phosphatase (TRAP)-positive multinucleated cells (P<0.05 for 5 and 10 µg/ml PEE, P<0.01 for 25 and 50 µg/ml PEE), without cytotoxic effects. Furthermore, the expression of differentiation-related marker genes, including TRAP, Oscar, Cathepsin K, dendrocyte expressed seven transmembrane protein, ATPase H+ Transporting V0 Subunit D2 and NFATc1, were markedly suppressed. PEE induced a transient increase in free cytoplasmic Ca2+ ([Ca2+](i)) mobilization via voltage-gated Ca2+ channels and PLC-sensitive pathways. Transient [Ca2+](i) increase consequently resulted in the suppression of c-Fos, CREB and NFATc1 activities. These findings highlight the potential use of PJ in treating bone disorders caused by osteoclast overgrowth.